Bridging narrative and locality in mobile-based augmented reality educational activities: Effects of semantic coupling on students’ immersion and learning gains - Georgiou, Yiannis; Kyza, Eleni A. (My University, 2021)
Despite the rapid development of mobile-based Augmented Reality (AR) apps, little is yet known about how we can facilitate immersion and learning in AR contexts. This study investigated the hypothesis that greater coupling between physical space and the narrative of the AR learning activity can result in increased levels of immersion and students’ conceptual learning gains. Prior studies investigating the coupling effect are limited, inconclusive and primarily focused on adult populations. The present study investigated the effects of two types of coupling (strong/loose) on middle school students’ experienced immersion and conceptual learning gains, in the context of a narrative-based AR science education intervention. Forty-five middle school students participated in this study: Students in Condition 1 (n = 22) participated in an AR activity with strong coupling between narrative and the physical space, while students in Condition 2 (n = 23) participated in a loose coupling version of the activity. The data corpus consisted of baseline data, questionnaires investigating students’ immersion and conceptual learning gains, and post-activity interviews. Findings showed higher conceptual learning gains and increased immersion for the students participating in the strong coupling condition than for the students in the loose coupling condition. We discuss these findings and their implications, and we highlight questions for future research.
Keywords: Immersion; Learning; Locality; Mobile-based AR apps; Narrative; Semantic coupling